Reconnaissance based damage survey of buildings in Kathmandu valley: An aftermath of 7.8 Mw, 25 April 2015 Gorkha (Nepal) earthquake. (January 2016) - Shakya, Manjip; Kawan, Chandra Kiran
Abstract: The recent high-intensity 2015 Gorkha (Nepal) earthquake, has caused not only a substantial death toll and huge economic losses, but also heavy damage to many public residential buildings. Both URM and RC buildings suffered low to heavy destruction. Each earthquake places buildings, in the affected area, to an earthquake withstand test and provides an opportunity to learn lessons for future preparedness to encounter the challenge of disaster. The Gorkha earthquake sequences delivered unprecedented opportunity to augment the understanding on seismic performance of public residential buildings. Along with presenting the seismicity and losses suffered during the earthquake, the current paper highlights earthquake induced damages to residential buildings in Kathmandu valley, both URM and RC buildings. This paper is also motivated to point out the faintness in past to current constructional practice of residential buildings and convey awareness to stake holders for future safer building construction practice. Highlights: Summary of seismicity and losses induced by the 2015 Gorkha earthquake is presented. Discussion of construction techniques, rules and detailing of RC and URM buildings in Kathmandu valley. Failure mode and damage pattern for residential buildings in Kathmandu valley due to the 2015 Gorkha earthquake are identified. Critical aspect for the devastation of RC and URM buildings is identified. Suggestion for the future construction techniques is discussed.